A Prospective, Ex Vivo Trial of Endobronchial Blockade Management Utilizing 3 Commonly Available Bronchial Blockers. (December 2019) - Gilbert, Christopher R.; Mallow, Christopher; Wishire, Candice L.; Chang, Shu-Ching; Yarmus, Lonny B.; Vallieres, Eric; Haeck, Katherine; Gorden, Jed A.
Abstract : BACKGROUND: Lung isolation with bronchial blockers is a well-described and accepted procedure, often described for use during the management of massive hemoptysis. Recommendations for balloon inflation are sparse, with some advocating for saline whereas other suggest air, including the manufacturers. We sought to evaluate the optimal method for balloon inflation in an ex vivo trial. METHODS: We performed a prospective trial utilizing 3 commercially available bronchial blockers commonly described for use in lung isolation and massive hemoptysis management. We utilized the Arndt Endobronchial Blocker (Cook Medical), the Cohen Tip Deflecting Endobronchial Blocker (Cook Medical), and the Fogarty Venous Thrombectomy Catheter (Edwards LifeSciences). Balloon size and deflation assessment were tested within 3 different scenarios comparing air versus saline. Welch t test was performed to compare means between groups, and a generalized estimating equation model was utilized to compare balloon diameter over time to account for correlation among repeated measures from the same balloon. RESULTS: All 3 endobronchial blocker systems were observed in triplicate. During free-standing balloon inflation, all 3 endobronchial systems displayed a greater degree of balloon deflation over time with air as opposed to saline ( P < .001). Within a stent-based model, inflation with air of all 3 endobronchial systems, according to manufacturer recommendations, demonstrated significantly decreased time until fluid transgression occurred when compared to a saline model ( P < .001). Within a stent-based model, inflation with air, according to clinical judgment, demonstrated significantly decreased time until fluid transgression in the Arndt ( P = .016) and the Fogarty ( P < .001) system, but not the Cohen ( P = .173) system, when compared with saline. CONCLUSIONS: The utilization of saline for balloon inflation during bronchial blockade allows for more consistent balloon inflation. The use of saline during balloon inflation appears to delay passive, spontaneous balloon deflation time when compared to air during a model of endobronchial blockade. The approach of saline inflation should be tested in humans to demonstrate the overall applicability and validity of the current findings.